2021
DOI: 10.3390/fermentation7040204
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Polyisoprene Can Mitigate Climate Change and Deforestation in Expanding Rubber Production

Abstract: Biomass is a promising renewable feedstock to produce polyisoprene for the rubber industry. Through metabolic engineering, sugars derived from pretreated and hydrolyzed cellulose and hemicellulose can be directly fermented to isoprene to produce rubber. Here we investigate the life cycle environmental impact of isoprene fermentation to produce bio-polyisoprene from agricultural residues (of Zea mays L.). Results show that the greenhouse gas (GHG) intensity of bio-polyisoprene (−4.59 kg CO2e kg−1) is significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…While the focus of this study is the techno-economic and life cycle GHG emission impact of DMCO jet fuel, multiple other life cycle impact assessment (LCIA) metrics that affect human health and the environment are critical for investment decisions. Our previous research 84 evaluated nine midpoint LCIA metrics using ReCiPe 2016 (ref. 85) for a biorefinery producing isoprene, corresponding with all cradle-to-isoprene process steps in the DMCO life cycle, including the lignin-fed boiler, which was the source of elevated air particulate matter (PM2.5), an indicator of air quality, and slightly high terrestrial acidification, which is also attributed to the lignin boiler.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the focus of this study is the techno-economic and life cycle GHG emission impact of DMCO jet fuel, multiple other life cycle impact assessment (LCIA) metrics that affect human health and the environment are critical for investment decisions. Our previous research 84 evaluated nine midpoint LCIA metrics using ReCiPe 2016 (ref. 85) for a biorefinery producing isoprene, corresponding with all cradle-to-isoprene process steps in the DMCO life cycle, including the lignin-fed boiler, which was the source of elevated air particulate matter (PM2.5), an indicator of air quality, and slightly high terrestrial acidification, which is also attributed to the lignin boiler.…”
Section: Resultsmentioning
confidence: 99%
“…85) for a biorefinery producing isoprene, corresponding with all cradle-to-isoprene process steps in the DMCO life cycle, including the lignin-fed boiler, which was the source of elevated air particulate matter (PM2.5), an indicator of air quality, and slightly high terrestrial acidification, which is also attributed to the lignin boiler. Batten et al 84 used the biorefinery mass balance audit from an Aspen Plus simulation by Humbird et al 62 to predict air pollutant emissions for a corn stover-to-ethanol biorefinery that was not equipped with air pollution controls. However, as noted in an earlier analysis by Spatari et al , 86 a biorefinery would not be permitted to emit uncontrolled VOC, CO or NO x emissions and would be required to invest in air pollutant controls, which would raise capital costs, and possible air quality impacts could be mitigated.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of benefit, researchers suggested that bio-based polyisoprene is able to significantly reduce greenhouse gas emissions by close to 300% as compared to synthetic rubber. In addition, land use intensity of bio-based polyisoprene is 84% lower than that from rubber tree plantations [23].…”
Section: Isoprene From Simple Sugarmentioning
confidence: 94%
“…The market of isoprene is estimated to be approximately 4 billion USD by 2025, growing at a compound annual growth rate more than 5% [22]. Today, bio-based polyisoprene is experiencing higher demand due to increase in awareness of sustainability and climate issues resulting in major tire companies like Michelin, Bridgestone and Goodyear choosing to partner with biotech companies to seek alternatives for isoprene supply [23]. In this regard, biological solutions could reduce future dependence on petroleum and is expected to contribute reducing carbon dioxide, widely considered to be a cause of global warming.…”
Section: Isoprene From Simple Sugarmentioning
confidence: 99%
“…The categories within ReCiPe allow comparing key global environmental, resource consumption, and human health ecosystem impacts of the two alternative production routes. The ReCiPe 2016 hierarchist method has been widely used to evaluate and benchmark multiple chemicals and production routes, prospective water infrastructure, treatment recovery processes, , emerging biochemicals and biopolymers, and renewable energy materials, processes, and planning. , …”
Section: Life Cycle Inventory (Lci) Analysismentioning
confidence: 99%